2012
DOI: 10.1177/230949901202000307
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Hip Screw Blade Fixation for Intertrochanteric Hip Fractures

Abstract: The 30-day and one-year mortality rates were 5% and 20%, respectively. At the one-year follow-up, 81 patients were available, and all fractures had healed without varus deformity. The mean tip-apex distance was 14.1 (range, 5.7-31.1; SD, 4.3) mm. The mean femoral shortening was 4.9 (range, 0-20.2; SD, 4.8) mm. The mean Parker score decreased to 3.8 at one-year follow-up from 5.9 before injury (p<0.001). There was one loss of fixation secondary to a non-traumatic subcapital fracture at 3 months, for which a bip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…O'Neil et al found that DHS blade has greater rotational stability than DHS [24]. Leung et al had also proven the effectiveness of DHS blade in a case series with 1% failure rate [25]. In this study, we found that DHS blade had better antidisplacement ability at CA and CC position and better antirotational ability at IC position than conventional DHS.…”
Section: Discussionsupporting
confidence: 59%
“…O'Neil et al found that DHS blade has greater rotational stability than DHS [24]. Leung et al had also proven the effectiveness of DHS blade in a case series with 1% failure rate [25]. In this study, we found that DHS blade had better antidisplacement ability at CA and CC position and better antirotational ability at IC position than conventional DHS.…”
Section: Discussionsupporting
confidence: 59%
“…It could be kept in the human body for a long time and is one of the first-choice internal fixator for clinical treatment of ITF at present [2,20]. The sliding screws and side plates of the DHS internal fixator are firmly fixed to the proximal end of the fracture with strong flexural strength, better medial support effect, thus being positive for hip fracture treatment [3,4,21]. However, in clinical application, concerning the effect of patients' ages, fracture types, reduction effects, and fixed positions, DHS fixation might bring complications such as screws breaking through the femoral head, screws cutting femoral head, coxa vara, screws loosening, and steel plates pulling out [5,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Since 1970, it has been widely used globally and was refined by the Swiss Society of Internal Fixation later, with a short abbreviation as DHS. At present, DHS has been recognized as the gold standard for stable ITF treatment, with features such as firm fixation, easy-to-perform and confirmative efficiency [2][3][4]. As its wide application, some accompanying failures such as femoral head cutting, fracture translocation due to too much hip screw sliding, fracture unhealing, and injured limb shortening [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…At the one-year follow-up, 81 patients were available, and all fractures had healed without various deformities [19]. There was one loss of fixation (1% device failure) secondary to a non-traumatic sub-capital fracture at 3 months, for which a bipolar hemi-arthro-plasty was performed.…”
Section: Screw Cutout and Device Failurementioning
confidence: 99%